The Role of Financial Accounting in Measuring the Impact of ESG Disclosure on Firm Value - Perdana, Buyung Cahya; Dewianawati, Dwi; Indrianto, Dian; Setiawan, Erry (SAFE-Network, 2025)
This study examines the mediating role of financial accounting in the relationship between ESG disclosure and firm value. The sample consists of 82 firm-year observations from non-financial companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023. Firm value is measured using Tobin’s Q, Price-to-Book Value, and Market-to-Book Ratio. ESG disclosure is assessed using Bloomberg/Refinitiv ESG scores and Global Reporting Initiative (GRI)-based content analysis. Financial accounting is proxied by earnings quality, value relevance, timeliness, and conservatism. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that ESG disclosure has a significant positive effect on both financial accounting and firm value. Financial accounting also has a significant positive effect on firm value and mediates the ESG–firm value relationship. The findings confirm that ESG disclosure contributes to firm valuation when accompanied by credible financial accounting practices. This study contributes to the sustainable finance literature by identifying the role of financial accounting as a mediator and provides practical insights for managers and regulators to strengthen integrated reporting practices.